Cinico-Epidemiological Profile of Vitiligo Patients in Dr. Hasan Sadikin General Hospital Bandung (Majalah Kedokteran Bandung, 2017)
Vitiligo is the most common hypopigmentation disorder; however, until now there iss no comprehensive epidemiological-clinical study of vitiligo in Indonesia. A descriptive study  using a questionnaire among vitiligo patients in Dr. Hasan Sadikin General Hospital Bandung was conducted to determine the clinical findings, socio-demographic factors, coexisting autoimmune disorders, and severity of disease. All vitiligo patients were recruited during the period of February 2012 to April 2014 from the Dermatology Outpatient Clinic of Dr. Hasan Sadikin General Hospital Bandung, as well as from the Endocrinology and Rheumatology Clinic Department of Internal Medicine; Endocrinology and Allergy and Immunology Clinics Department of Child Health; and Department  of Nuclear Medicine the same hospital. We collected data on socio-demographic profiles, clinical profile, and severity of vitiligo based on Vitiligo European Task Force (VETF). Out of 242 patients, female patients made up the majority of the patients (66.12%). In addition, most patients  wereunder 20 years (33.47%) and experienced onset of vitiligo highest in the first decade of life (29.34%). About 19.42% had positive family history of vitiligo and only 6.2% had history of autoimmune diseases. The majority of patients (77.27%) had vulgaris type of vitiligo with  head-neck (35.36%) asthe most frequent initial site of onset. Based on VETF,  the skin affected was mostly below 10% of body surface area (82.23%), i.e. staging score of between 0–5 (57.44%), and spreading score of between >0–(+5) or 68.18%. It is concluded that vitiligo most commonly occurs in females with the highest onset of under 10-years old and strong relationship with genetic predisposition.T he affected area was relatively small, despite the high spreading score. [MKB. 2017;49(2):132–8]   Key words: Clinical profile, epidemiology, vitiligo  Profil Kliniko-Epidemiologi pada Pasien Vitiligo di RSUP Dr. Hasan Sadikin Bandung   Vitiligo merupakan kelainan hipopigmentasi tersering, tetapi hingga kini belum ada penelitian epidemiologi-klinik yang komprehensif di Indonesia. Penelitian deskriptif menggunakan kuesioner dilakukan pada pasien vitiligo di Rumah Sakit Dr. Hasan Sadikin Bandung untuk mengetahui gambaran klinis, faktor sosio-demografik, kelainan autoimun yang menyertai, dan keparahan penyakit. Seluruh pasien vitiligo dari periode Februari 2012 hingga April 2014 yang berkunjung ke poliklinik Kulit dan Kelamin Rumah Sakit Dr. Hasan Sadikin Bandung, serta poliklinik: Endokrinologi dan Rematologi, Ilmu Penyakit Dalam; Endokrinologi dan Alergi-imunologi, Ilmu Kesehatan Anak; serta Kedokteran Nuklir, diikutsertakan dalam penelitian. Data yang dihimpun mencakup keadaan sosiodemografi, klinik, dan keparahan vitiligo berdasar atas Vitiligo European Task Force (VETF). Dari 242 pasien, perempuan merupakan jenis kelamin terbanyak (66,12%), usia di bawah 20 tahun (33,47%), dan awitan vitiligo terjadi pada dekade pertama kehidupan (29,34%). Sekitar 19,42% memiliki riwayat vitiligo pada keluarga dan hanya 6,2% yang memiliki penyakit autoimun. Umumnya tipe vitiligo vulgaris (77,27%) dengan predileksi pertama pada kepala-leher (35,36%). Area kulit yang terkena berdasarkan VETF ialah di bawah 10% dari body surface area (82,23%), staging score 0–5 (57,44%), dan spreading score antara >0–(+5) atau 68,18%. Simpulan penelitian ini ialah vitiligo banyak mengenai perempuan, awitan tersering pada usia di bawah 10 tahun dengan predisposisi genetik yang tinggi, serta daerah yang terkena vitiligo relatif kecil meskipun spreading score-nya tinggi. [MKB. 2017;49(2):132–8]   Kata kunci: Epidemiologi, gambaran klinik, vitiligo
Keywords: Clinical profile; epidemiology; vitiligo